Rice husk combustion characteristics in a rectangular fluidized-bed combustor with triple pairs of chevron-shaped discrete ribbed walls - Suriya Chokphoemphun; Smith Eiamsa-ard; Pongjet Promvonge; Varesa Chuwattanakul (My University, 2019)
An experimental combustion work using the rice husk as a fuel was performed in a rectangular fluidized bed combustor with triple pairs of chevron-shaped discrete ribbed walls. The effect of percent excess air (EA = 40%–70%) on temperature distribution and gas emissions in a rectangular fluidized-bed combustor on combustion behaviors (temperature distributions inside the bed, exhaust gas emissions and combustion efficiency) is reported. The free-board had a rectangular shape which modified by increasing the chamber size from 300 × 100 mm2 to 600 × 200 mm2 or two times of the bottom chamber and 2400 mm in height. Triple pairs of rib configurations, namely, 30° chevron-shaped discrete ribbed walls were introduced and placed in the bottom part of the combustion chamber to generate counter-rotating vortices in the chamber. The results show that the fluidized bed combustor with 30° chevron-shaped discrete ribbed walls at 40% percent excess air provides the higher temperature than other of 861 °C. Among the studied excess air percentages, the highest combustion efficiency of 99.2% is obtained at EA = 60%. In addition, combustion at EA = 60% shows the lowest emissions CO, CO2, O2 and NOx of 236.8%Vol, 2.55 ppm, 13.53 %Vol, 110.2 ppm, respectively.
Keywords: Chevron (anatomy); Fluidized bed combustion; Thermochemical Biomass Conversion Processes